Local embeddability - Belegradek, O. (Algebra and Discrete Mathematics, 2012)
For an arbitrary class of algebraic structures we consider a notion of a structure locally embeddable to structures of the class. This generalizes the notion of a group locally embeddable to finite groups studied by Vershik and Gordon. We give various model-theoretic characterizations of such structures. Some of them generalize known group-theoretic results.